(untitled) (Journal of Asian Development Studies, 2025)
The paper attempts to investigate undergraduate EFL students’ attitudes toward learning English in terms of cognitive, affective, behavioural and aggregate dimensions. Based on their demographic profile, specifically their gender, the study examined how gender influences and impacts learners’ attitudes. Sixty EFL second-semester students participated in this study. The findings of the survey questionnaire revealed that the learners have relatively positive attitudes towards learning English. However, for comparing male and female students, the results showed no significant differences between the two groups. The findings have meaningful implications for curriculum design and policy-making in similar settings.